Moving toward a precise nutrition: preferential loading of seeds with essential nutrients over non-essential toxic elements - Khan, Mather A.; Castro-Guerrero, Norma A.; Mendoza-Cozatl, David (Frontiers in Plant Science, 2014)
Plants and seeds are the main source of essential nutrients for humans and livestock. Many advances have recently been made in understanding the molecular mechanisms by which plants take up and accumulate micronutrients such as iron, zinc, copper and manganese. Some of these mechanisms, however, also facilitate the accumulation of non-essential toxic elements such as cadmium (Cd) and arsenic (As). In humans, Cd and As intake has been associated with multiple disorders including kidney failure, diabetes, cancer and mental health issues. Recent studies have shown that some transporters can discriminate between essential metals and non-essential elements. Furthermore, sequestration of non-essential elements in roots has been described in several plant species as a key process limiting the translocation of non-essential elements to aboveground edible tissues, including seeds. Increasing the concentration of bioavailable micronutrients (biofortification) in grains while lowering the accumulation of non-essential elements will likely require the concerted action of several transporters. This review discusses the most recent advances on mineral nutrition that could be used to preferentially enrich seeds with micronutrients and also illustrates how precision breeding and transport engineering could be used to enhance the nutritional value of crops by re-routing essential and non-essential elements to separate sink tissues (roots and seeds).